The overtaking of undertaking: feminization and the changing gender type of funeral directing - Donley, Sarah (Kansas State University, 2014)
Despite the predictions that the influence of women into male-dominated fields would eventually eliminate women’s disadvantaged positions in paid work, most research finds that feminization results in the reconfiguration of gender inequality. These studies tended to investigate the material consequences and conditions of feminization and how the “gendering” of the occupation develops to justify the reconfiguration of inequality. Scholarship has begun to examine how individuals in occupations negotiate the existing occupational gender-type and how this shapes gender inequality in feminizing occupations. My dissertation takes up this call by looking at the relationship between gender-typing (i.e., how occupations or jobs come to be understood as appropriate for men or women) and feminization (i.e., women in a formerly male-dominated occupation) in the funeral industry. The funeral industry has traditionally been a male-dominated and gender-typed masculine occupation; however, since the 1970s funeral directing has been experiencing feminization. In recent history, women were not seen as appropriate for funeral directing. They were considered too physically and emotionally “unfit;” however, the movement of women into the occupation complicates how funeral directing was traditionally gender-typed. Using text excerpts about gender (n=101) from 35 funerary trade journal articles ranging from 1995-2013, my dissertation explores competing cultural beliefs about gender at the occupational-level (“old boy,” gender essential, gender blind, and gender-progressive) accompanying women’s movement into funeral directing. Through semi-structured interviews with twenty (11 women, 9 men) mortuary science students who are studying to become funeral directors and twenty-two (13 women, 9 men) licensed funeral directors, I explore how these occupational scripts about gender affect workplaces in terms of the workplace experiences (practices and hiring, the division of labor, relations between employees and supervisors) and educational experiences (occupational entry, structure and training); and how current and future funeral directors negotiate cultural gender beliefs about funeral directing to challenge existing explanations and create new explanations about women’s suitability for funeral directing. My findings indicate that occupational cultural beliefs about gender are both reproduced and challenged in workplace and educational settings and in how students and funeral directors negotiate cultural gender beliefs.
Keywords: Gender; Work; Occupations; Feminization; Inequality; Funeral Directing; Sociology (0626)